A „The Journey” társulattal Schubert nyomában - Elekes, Márta-Adrienne (Symbolon, 2025)
Following Schubert with "The Journey" Company There is no denying that the conference call published by the University of Arts of Târgu Mureș, which focuses on dance and movement, really managed to mention a wide variety of genres. However, this is clearly not among them. “Winter journey in song and dance. An extraordinary and particularly impressive interpretation of Schubert's master cycle in many respects: Juliane Banse sings and dances. The Winter Journey in dialogue with dancer István Simon - a dense and intense evening that, according to Andreas Heise, allows for a different musical approach, taking the audience on a multidimensional journey of sound and image,"" we read in the 2022 advertisement of the Wilhelma Theater in Stuttgart. Schubert's song cycle Winter Journey was presented by The Journey company in Târgu Mureș on March 18, 2023, in the Big hall of the Palace of Culture. The production promoted a fusion of dance, music, and singing, but knowing the musical work, the question rightly arises: how can abstract ideas in dance be represented through body contact and dance technique? The choreographer of The Journey's Schubert performance may have encountered a similar question. In his approach, he probably shared the opinion of Dietrich Fischer-Dieskau. The baritone singer speaks of a terrifying intensity, given the expression of suffering. This intensity forms the basis of Andreas Heise's choreographic realization, which ultimately turned out to be brilliant.